Characterization of carbapenemase-producing Gram-negative bacilli: first report of blaNDM-1 in Enterobacter cloacae - Manel Debabza; Raoudha Dziri; Abdelbasset Mechai; Amel Bouguessa; Naouel Klibi; Hadda Imene Ouzari (Journal of Infection in Developing Countries)
Introduction: The spread of multidrug-resistant bacteria, particularly carbapenem-resistant Gram-negative bacilli (CR-GNB), has become a serious challenge for clinicians due to limited therapeutic options. The aim of the study was to investigate the prevalence of carbapenemase production among clinical isolates recovered from 352 samples collected in Tebessa hospital, Algeria.